Effect of Apium Graveolens (Celery) Seed Extract on Serum Uric Acid Level of Hyperuricemic Rats and its Comparison with Allopurinol - Abdul Karim; Shabbir Ali bhatti; Noman Johnson; Mahreen Akhtar; Sundus Mona; Zartasha Safdar (Shalamar Medical & Dental College, Lahore, Pakistan, 2021)
Background: Plant derived medicines are widely used in traditional culture all over the world. Objectives: To determine the effect of Celery Seed Extract (CSE) on uric acid levels in hyperuricemic rats and to compare the effect of allopurinol and CSE. Methods: It was an animal experimental research study. Group A served as negative control whereas Group B served as positive control. CSE was given orally to three groups of rats (C, D, and E). One hour prior to administration of CSE; potassium oxonate was injected intraperitoneally in all groups except negative control to induce hyperuricemia. Similarly, group F was given allopurinol one hour after injection of potassium oxonate. Blood samples were collected for uric acid estimation. Results: It was found that administration of both CSE (group C, D, E) and allopurinol (group F) significantly lowered serum uric acid levels (p<0.001) as compared to positive control (group B). Serum uric acid lowering effect of both drugs CSE and allopurinol was found to be statistically significant on day 3rd and day 7th and was almost comparable. Conclusions: Celery seed extract significantly reduces serum uric acid levels in potassium oxonate-induced hyperuricemic rats and its uric acid lowering effect was comparable with that of allopurinol.